Reading Today (Book collections on Project MUSE., 2018)
New technologies are changing our reading habits. Laptops, e-readers, tablets and other handheld devices supply new platforms for reading, and we must learn to manage them by scrolling, clicking or tapping. Reading Today places reading in current literary and cultural contexts in order to analyse how these contexts challenge our conceptions of who reads, what reading is, how we read, where we read, and for what purposes? and then responds to the questions this analysis raises. Is our reading experience becoming a?flat? one? And does reading in a media environment favour quick reading? Alongside these questions, the contributors unpack emerging strategies of reading. They consider, for example, how paying attention to readers? emotional reactions as an indispensable component of reading affects our conception of the reading process. Other chapters consider how reading can be explored through such topics as experimental literature, the contemporary encyclopedic novel and the healing power of books.